Penguatan Sistem Pengelolaan Sampah Berbasis Komunitas melalui Pembangunan TPS (Tempat Penampungan Sementara) Desa Sunyalangu, Banyumas - Nita Sofia Rakhmawati; Dwi Sahidin; Valenstyano Wahyu Setiyawan; Mega Ayu Intan Nur’aini; Danu Damara; Ilham Hela Pratama (Universitas Muhammadiyah Semarang, 2026)
Household waste management at the village level remains a challenge due to limited facilities, low community participation, and the suboptimal implementation of community-based waste management systems. Sunyalangu Village, Karanglewas District, Banyumas Regency, with an estimated waste generation of approximately ±200 kg/day, did not yet have an adequate Temporary Waste Storage Facility (TPS), resulting in poorly coordinated waste management practices. This community service program aimed to strengthen the community-based waste management system through the construction of a TPS, the provision of waste segregation facilities, and community education and assistance. The program was implemented over one month involving 50 residents, the Community Self-Help Group (KSM), and village officials through initial surveys, TPS construction, education, assistance, and program evaluation using pre-test and post-test questionnaires, observations, and interviews. The results showed the successful construction of one segregated TPS unit managed by the village KSM. Community participation in household waste segregation increased from 35% to 70%, regular TPS utilization increased from 30% to 65%, and community involvement in village clean-up activities increased from 40% to 68%. Community knowledge regarding waste management also improved, particularly related to waste types, the importance of waste segregation, and the function of the TPS. Observation results further indicated a reduction in illegal waste disposal practices within the village environment. Although the volume of managed waste has not yet been quantitatively measured, improvements in facilities, community participation, and governance indicate that the community-based approach has the potential to support a more structured and sustainable village waste management system.